2006
DOI: 10.2307/4134557
|View full text |Cite
|
Sign up to set email alerts
|

Signaling to the Enemy? Body Pattern Expression and Its Response to External Cues During Hunting in the Cuttlefish Sepia officinalis (Cephalopoda)

Abstract: Cuttlefish can rapidly alter their appearance by using neurally controlled chromatophore organs. This ability may provide a window into their cognitive capacity. We test whether the changes in body pattern that occur during hunting depend on context. If they do, then it may be possible to use these changes to study cephalopod cognition while the animal is engaged in ecologically relevant tasks. We found consistent individual differences in the tendency of cuttlefish to hunt with the first two arms raised. We a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 30 publications
4
36
0
Order By: Relevance
“…In the present study, cuttlefish showed different body patterns and behaviors during trials when predators were apparent (with bluefish) than when they were not (with flounder). Adamo et al (2006) reported similar results after cuttlefish were exposed to a (model) predator compared to when animals were allowed to forage without a disturbance. Bipedal locomotion was shown by cuttlefish during a single trial with bluefish; previously, this behavior has been reported only in the two octopus species Abdopus aculeatus and Amphioctopus marginatus (Huffard et al, 2005;Huffard, 2006).…”
Section: Cuttlefish Foraging-related Behaviorssupporting
confidence: 62%
See 2 more Smart Citations
“…In the present study, cuttlefish showed different body patterns and behaviors during trials when predators were apparent (with bluefish) than when they were not (with flounder). Adamo et al (2006) reported similar results after cuttlefish were exposed to a (model) predator compared to when animals were allowed to forage without a disturbance. Bipedal locomotion was shown by cuttlefish during a single trial with bluefish; previously, this behavior has been reported only in the two octopus species Abdopus aculeatus and Amphioctopus marginatus (Huffard et al, 2005;Huffard, 2006).…”
Section: Cuttlefish Foraging-related Behaviorssupporting
confidence: 62%
“…Cuttlefish are known to show complex displays as antipredator defenses, sexual displays, hunting displays, and as alarm signals to conspecifics (Moynihan and Rodaniche, 1982;Hanlon and Messenger, 1988;Adamo and Hanlon, 1996;Adamo et al, 2006;Langridge et al, 2007). In control trials where no predators were present, cuttlefish showed several body patterns that camouflaged them against natural substrates consisting of sand, rocks, and pebbles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity of chromatic components differed both within and between cuttlefish during the experiment, but the combinations of characteristic chromatic components in each body pattern were consistent, which enabled us to distinguish the body patterns from each other. Four body patterns were identical to those classified as "uniform light", "disruptive", "all dark" and "eyespots" in many previous studies using S. officinalis (e.g., Adamo et al, 2006;Barbosa et al, 2007;Mäthger et al, 2007;Langridge et al, 2007;Langridge, 2009). Body patterns similar to two body patterns that we classified as "vertical stripe" and "center circle" have been reported in several previous studies (see Hanlon and Messenger, 1988;Lee et al, 2010).…”
Section: Discussionsupporting
confidence: 54%
“…Most notable are their advanced abilities to colour change and camouflage (Hanlon 2007;Barbosa et al 2008;Mathger et al 2008), exhibit postural displays (Hanlon et al 1999;Huffard 2006;Bush et al 2009) and use ink to confuse both menacing predators and conspecifics (Wood et al 2008). While cephalopods are known to use deimatic and protean displays towards predators (Moynihan & Rodaniche 1982;Hanlon & Messenger 1988, 1996Adamo et al 2006;Langridge 2009), few studies have evaluated the conditions and types of predators that evoke these defences during predator-prey interactions.…”
Section: Introductionmentioning
confidence: 99%